2002
DOI: 10.1109/tgrs.2002.804834
|View full text |Cite
|
Sign up to set email alerts
|

Automatic classification of land cover on Smith Island, VA, using HyMAP imagery

Abstract: Abstract-Automatic land cover classification maps were developed from Airborne Hyperspectral Scanner (HyMAP) imagery acquired May 8, 2000 over Smith Island, VA, a barrier island in the Virginia Coast Reserve. Both unsupervised and supervised classification approaches were used to create these products to evaluate relative merits and to develop models that would be useful to natural resource managers at higher spatial resolution than has been available previously. Ground surveys made by us in late October and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 35 publications
0
38
0
Order By: Relevance
“…Ground based reflectance measurements were used to calibrate the imagery data based on target end members collected with an ASD FieldSpec Pro Full range reflectance radiometer (Analytical Spectral Devices Inc., Boulder, Colorado, USA). Classification of individual plant species followed methods demonstrated with coastal vegetation (Bachmann et al 2002, Bachmann 2003. Field reflectance spectra for individual species were collected and wavelength bands identified that distinguished species.…”
Section: Methodsmentioning
confidence: 99%
“…Ground based reflectance measurements were used to calibrate the imagery data based on target end members collected with an ASD FieldSpec Pro Full range reflectance radiometer (Analytical Spectral Devices Inc., Boulder, Colorado, USA). Classification of individual plant species followed methods demonstrated with coastal vegetation (Bachmann et al 2002, Bachmann 2003. Field reflectance spectra for individual species were collected and wavelength bands identified that distinguished species.…”
Section: Methodsmentioning
confidence: 99%
“…Sources of nonlinearity include: (1) nonlinear variations in reflectance produced by variations in sun-canopy-sensor geometry in the landscape [15] [9], (2) multi-path scatter among sub-pixel constituents [12] [14], violating the traditional linear mixing assumptions, (3) the variable presence of water, an attenuating medium [11] in the scene. Some of the errors that we observed in mapping products that we previously derived in [2] [3] became the motivation for finding new methods of modeling nonlinear structure in hyperspectral data [4]. In the next two subsections, we give a brief overview of the approach that we presented in [4] as a preamble to introducing improvements.…”
Section: A Nonlinearity In Hyperspectral Imagerymentioning
confidence: 99%
“…Note that the definition of "tractable" was addressed in [4], but improved scaling presented in Section II expands the scale of what is considered a computationally feasible tile size. The ISOMAP portion of the computations involves the following steps: (1) given a specified metric such as Euclidean, spectral angle, or some other appropriate choice, determine the spectral neighborhoods (initial sparse neighborhood graph) where linearity holds, maintaining a list for each sample of its neighbors and metric distances; (2) at each sample, for all distances outside the neighborhood, use Dijkstra's algorithm [7] [16] with a minimum priority queue to relax the closest edge not already attached to the graph d G to compute the shortest nonlinear path (geodesic) distance to all other samples (note that this is a graph calculation and that the metric, therefore, is not involved here but is only evaluated in step (1) inside the neighborhood); (3) if there are any remaining distances which can not be connected in the distance graph, attach pockets of isolated points to each other in the graph by find the closest linear distance between pairs of isolated pockets, thus preserving the geodesic structure of each and ensuring a minimal spanning tree [4] 1 ; after attaching all points symmetrize to ensure consistency of paths in both directions; (4) with the full NxN (N=number of spectral samples) geodesic distance matrix calculated in steps (1) and (2), compute the second order variation in the geodesic distances,…”
Section: B Manifold Coordinate Representationsmentioning
confidence: 99%
See 2 more Smart Citations